Policy Capacity Meets Politics; Comment on "Health Reform Requires Policy Capacity" - Patrick Fafard (Kerman University of Medical Sciences, 2015)
It is difficult to disagree with the general argument that successful health reform requires a significant degree of policy capacity or that all players in the policy game need to move beyond self-interested advocacy. However, an overly broad definition of policy capacity is a problem. More important perhaps, health reform inevitably requires not just policy capacity but political leadership and compromise.